A comprehensive mutation study in wide deep-rooted R1b Serbian pedigree: mutation rates and male relative differentiation capacity of 36 Y-STR markers. (July 2019) - Čokić, Vladan P.; Kecmanović, Miljana; Zgonjanin Bosić, Dragana; Jakovski, Zlatko; Veljković, Aleksandar; Katić, Srdjan; Keckarević Marković, Milica; Keckarević, Dušan
Highlights: 120 male contemporaries (6349 pairs of relatives) related by 1–20 meiosis (overall 485) were genotyped using 36 Y-STRs. An average mutation rate was 10.06 × 10 −3 (95% CI: 8.65 × 10 −3 - 11.61 × 10 −3 ). RM13, Yfiler + and PPY23 differentiated 95.9%, 65.5% and 57.4% pairs of relatives. Extra-pair paternity rate was 11.9 × 10 −3 (95% CI: 4.4 × 10 −3 - 25.8 × 10 −3 ). A positive correlation between the fathers' ages and mutability rates was observed. Abstract: Haplotyping of Y-chromosomal short tandem repeats (Y-STRs) reflects the paternal lineage, although, the father-son pair profiles may differ due to the germline mutations. In order to discriminate between closely related males in criminal cases, as well as for the correct application of Y-STRs in the paternity/kinship analysis and determination of the most recent common ancestor in the familial searching or genealogy research, the assessment of mutation rates of routinely used Y-STRs is of a great importance. We genotyped 120 males belonging to one wide deep-rooted pedigree separated by 1–20 meiosis. The haplotypes of analyzed males distributed over 12 different families (according to their surnames), with 113 originating from one ancestor, and the remaining 7 from the second, closely related to the previous one, belong to the R1b haplogroup. The analysis was performed using Powerplex® Y23 kit, Yfiler ™ plus kit and 13 rapidly mutating (RM13) Y-STRs. In 20, 855 allele transmissions, 175 mutations (61% repeat losses and 39% gains) and one gene conversion event were found at 25 out of 36 markers. The medians of locus-specific mutation rates estimated using the Bayesian approach ranged from 1.42 × 10 −3 (95% credible interval (CI): 0.05 × 10 −3 - 7.56 × 10 −3 ) for loci with no observed mutations to 130.91 × 10 −3 (95% CI: 102.91 × 10 −3 - 162.78 × 10 −3 ) for DYF399S1, with a median rate across all 36 markers of 10.06 × 10 −3 (95% CI: 8.65 × 10 −3 - 11.61 × 10 −3 ). In 6349 male relative pairs, the 36 Y-STR set distinguished 98.4% relative pairs by at least one mutation, compared to 95.9%, 65.5% and 57.4% for RM13, Yfiler ™ plus, and Powerplex® Y23 set, respectively. The extra-pair paternity rate was estimated at 11.9 × 10 −3 (95% CI: 4.4 × 10 −3 – 25.8 × 10 −3 ) fitting within the range reported for some European populations. A significant positive correlation was observed between fathers' ages at the time of the Y chromosome transmission and mutability rates (R 2  = 0.9495, p = 0.0256), with more significant results when analyzing RM markers (R 2  = 0.9827, p = 0.0087).